Hierarchial Identity-Based Encryption Scheme from Multilinear Maps - Hao Wang; Zhihua Zheng; Lei Wu (2014 Tenth International Conference on Computational Intelligence and Security, 2014)
Identity-based encryption (IBE) is an important primitive of identity-based cryptography. As such it is a type of public-key encryption in which the public key of a user is some unique information about the identity of the user (e.g. a user's email address). Hierarchical identity-based encryption (HIBE) provides more functionality by forming levels of an organizational hierarchy. A user can delegate secret keys to descendant identities at lower levels, but cannot decrypt messages intended for a recipient that is not among its descendants. In this paper, we construct a new HIBE scheme in a generic leveled multilinear map setting and prove its security under multilinear decisional Diffie-Hellmanin assumption in the selective-ID model.